Self-Inflicted Hand Amputation without Replantation in a Patient with Body Integrity Identity Disorder: A Case Report. Issue 3 (July 2021) - Ramkumar, Dipak B.; Brown, Marcel G.; Lewis, Chad Y.; Warren, Celestine E.; Fortney, Thomas A.; Warhold, Lance G.
Abstract : Case: We describe a patient who self-amputated his hand using a log splitter, because of a long-standing belief that the limb "did not belong to him." On admission, he refused replantation and was found to be nonpsychotic. He was diagnosed with body integrity identity disorder (BIID) and declared competent to make his own medical decisions. A revision amputation was performed. Conclusion: BIID is a challenging diagnosis that physicians treating traumatic injuries should be aware of. Many ethicists support elective amputation as a definitive treatment, because of potential harm reduction and because BIID does not respond to conservative modalities such as pharmacotherapy.